USE OF ULTRASONOGRAPHY FOR CONFORMATION OF CENTRAL VENOUS CATHETER PLACEMENT FOR HEMODIALYSIS - SINGLE CENTER EXPERIENCE - Pushevski, Vladimir; Spasovska-Vasilova, Adrijana; Milenkova, Mimoza; Janevski, Zoran; Trajceska, Lada; Rambabova Bushljetikj, Irena; Shpishikj Pushevska, Ana Marija; Dejanov, Petar (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
Conformation for safe placement of central venous catheter for hemodialysis and exclusion of pneumothorax is done with chest x ray. However, this procedure is time consuming, so in order to shorten this time several attempts have been tried to use bedside ultrasound. To use bedside ultrasonography to confirm tip location of central venous catheter and rule out pneumothorax.  The second aim was to compare these results with plain chest x ray. In 50 patients on hemodialysis central venous catheter were inserted in internal jugular vein or subclavian vein under ultrasound guidance. After insertion, a subxiphoid 4 chamber view was obtained looking to detect turbulence or microbubbles shortly after 10ml saline flush through catheter. Then, ultrasound of the patient's chest was performed to exclude pneumothorax. After the exam, a plain chest x raywas performed for the conformation of the findings. From 50 placed hemodialysis catheters, 47 were adequately placed. All catheters were identified with the use of ultrasound. The tip of the 3 misplaced catheters could not be detected with the use of ultrasound. No pneumothorax was observed. The average time for detection of correct catheter placement was much faster with the use of ultrasound compared with chest x ray (11,5min and 80 min, accordingly). The use of bedside ultrasound for conformation of central venous catheter placement and excluding pneumothorax is as accurate as with chest radiography, but it is can be done much faster. Keywords: catheter placement, bedside ultrasonography, hemodialysis, microbubbles, pneumothorax. https://doi.org/10.55302/JMS2251049p